Trends in the distribution and abundance of cetaceans from aerial surveys in Icelandic coastal waters, 1986-2001 - Pike, Daniel G; Paxton, Charles GM; Gunnlaugsson, Thorvaldur; Víkingsson, Gísli A (NAMMCO Scientific Publications, 2009)
Aerial surveys were carried out in coastal Icelandic waters 4 times between 1986 and 2001 as part of the North Atlantic Sightings Surveys. The surveys had nearly identical designs in 3 of the 4 years. The target species was the minke whale (Balaenoptera acutorostrata) but all species encountered were recorded. Sighting rate and density from line transect analysis were used as indices of relative abundance to monitor trends over the period, and abundance estimates corrected for perception biases were calculated for some species from the 2001 survey. More than 11 species were sighted, of which the most common were the minke whale, humpback whale (Megaptera novaeangliae), dolphins of genus Lagenorhychus, and the harbour porpoise (Phocoena phocoena). Minke whales and dolphins showed little change in distribution or abundance over the period. There were an estimated 31,653 (cv 0.30) dolphins in the survey area in 2001. Humpback whales increased rapidly at a rate of about 12%, with much of the increase occurring off eastern and northeastern Iceland. In 2001 there were an estimated 4,928 (cv 0.463) humpback whales in the survey area. The relative abundance of harbour porpoises decreased over the period, but estimates for this species were compromised by uncorrected perception biases and poor coverage. The ecological and historical significance of these findings with respect to previous whaling activities and present-day fisheries is discussed.